2012
DOI: 10.1109/tuffc.2012.2154
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound array transmitter architecture with high timing resolution using embedded phase-locked loops

Abstract: Abstract-Coarse time quantization of delay profiles within ultrasound array systems can produce undesirable sidelobes in the radiated beam profile. The severity of these sidelobes is dependent upon the magnitude of phase quantization error -the deviation from ideal delay profiles to the achievable quantized case. This paper describes a method to improve inter channel delay accuracy without increasing system clock frequency by utilising embedded Phase-Locked Loop (PLL) components within commercial Field Program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…1), which was based on the Ultrasound Array Research Platform architecture reported previously [57]. The system is capable of driving transducer loads with excitation signal amplitudes up to ±100 V using a commercially available integrated circuit (MAX4811, Maxim Integrated, San Jose CA, USA).…”
Section: B Ultrasound Systemmentioning
confidence: 99%
“…1), which was based on the Ultrasound Array Research Platform architecture reported previously [57]. The system is capable of driving transducer loads with excitation signal amplitudes up to ±100 V using a commercially available integrated circuit (MAX4811, Maxim Integrated, San Jose CA, USA).…”
Section: B Ultrasound Systemmentioning
confidence: 99%
“…In order to study the effectiveness of FDMAS beamforming technique on PWI and CPWI, several laboratory experiments have been carried out on wire and multipurpose phantom with UARP II [4] [5]. Our first experiment was carried out on 120µm wire phantom located from 20 mm until 60 mm depth with 10 mm spacing between them as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A 128-element L3-8/40EP medical probe with 0.3048 mm centre-to-centre distance was used during the experiments, driven by the Ultrasonic Array Research Platform (UARP) developed by the ultrasound group [14]- [16]. The UARP provides the control for 96 channels.…”
Section: Methodsmentioning
confidence: 99%